EFFECT OF GENDER ON FARMERS’ OWNERSHIP, CONTROL AND ACCESSIBILITY TO CLIMATE CHANGE ADAPTATION RESOURCES IN SOUTHWEST NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
The ability to access, control and own adaptation resources is a critical factor in determining rural farmersâ€™ adaptive potential and decision-making towards adaptation to climate change.  This study investigated the effect of gender on farmersâ€™ accessibility, control and ownership of climate change adaptation resources in Ogun and Ekiti States respectively, Nigeria. Three hundred and fifty eighty men (358) and (222) women farmers were randomly selected through a multi-stage sampling procedure. A pre-tested questionnaire was used to obtain data and analysed with frequency counts, means, percentages, Chi-square.  A positive and statistically significant association (P
Keywords: Access, control, ownership, climate change, capacity